Consumer Behaviour at the Generic Level: Theoretical Perspectives - Rahmat Hidayat (Faculty of Psychology Universitas Gadjah Mada, 2014)
Suppose you had unexpectedlyreceived some money, for instance a gift ora lottery prize. What would you like to dowith the money? Why the action you choseto do is of much importance to you? Whatwould you like to achieve by that action?This is a simple illustration of the genericlevel of consumer decision making,henceforth the generic level. It is importantto note that neither money nor unexpec-tedness defines the generic level. Althoughthere are plenty of examples of receiving awindfall, gifts and lottery prizes being twoof them, the generic level also concernssituations when expectations rule. Forexample, people may expect to receive abumper bonus, an extra profit, a taxreturn, gain excessive money from a pre-vious budget, or even to inherit somevaluable assets from their beloved parents.To a certain degree, people in suchsituations must ponder of the differentways to utilize the money. The definingfeatures of the generic level concern themental processes of decision making inwhich an individual is trying to allocate aconsumer resource into different cate-gories of activities (Van Veldhoven &Groenland, 1993).